2020
DOI: 10.1021/acsami.0c08649
|View full text |Cite
|
Sign up to set email alerts
|

Highly Oil-Repellent Thermoplastic Boundaries via Surface Delivery of CF3 Groups by Molecular Bottlebrush Additives

Abstract: We fabricated thermoplastic surfaces possessing extremely limited water and oil wettability without employment of long-chain perfluoroalkyl (LCPFA) substances. Namely, by taking advantage of the structure and behavior of original oleophobic perfluoropolyether (PFPE) methacrylate (PFM) molecular bottlebrush (MBB) additive we obtained polymeric surfaces with oil contact angles well above 80° and surface energy on the level of 10 mN/m. Those angles and surface energies are the highest and the lowest respective va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15][16][17] It is difficult to modify the structure of perfluorinated compounds, which are mainly modified by perfluorinated derivatives in a late stage. 18 Besides, more by-products are obtained through the conventional fluorination reaction. 19 It also takes time and is economically costly from detection to environmental and health assessments, as well as due to technical secrecy and other considerations, 14,20,21 so research regarding the development of relatively efficient and safe perfluorinated substitutes is progressing slowly.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] It is difficult to modify the structure of perfluorinated compounds, which are mainly modified by perfluorinated derivatives in a late stage. 18 Besides, more by-products are obtained through the conventional fluorination reaction. 19 It also takes time and is economically costly from detection to environmental and health assessments, as well as due to technical secrecy and other considerations, 14,20,21 so research regarding the development of relatively efficient and safe perfluorinated substitutes is progressing slowly.…”
mentioning
confidence: 99%
“…The difference could be connected to the surface energy of the repeating units constituting macromolecular chains. To this end, we estimated surface energies and their (polar and dispersive) components (SI: S6) for the molecular segments constituting FOPUs using algorithms reported elsewhere [20,36]. The calculated values are presented in SI, Table S4.…”
Section: Water and Oil Repellency Of Hfopu-1 And Mfopu-1mentioning
confidence: 99%
“…The surface energy values estimated from the contact angle of hexadecane are close, but to some extent different from the ones obtained by the Owens-Wendt method utilizing both WCA and HDCA. We associate this difference with the differences in the size of the wetting liquids, which plays a significant role in the wettability of polymer surfaces [20,21,36]. Based on molecular weight and chemical structure, the size of water molecule is about an order of magnitude smaller than that of hexadecane.…”
Section: Water and Oil Repellency Of Hfopu-1 And Mfopu-1mentioning
confidence: 99%
See 1 more Smart Citation
“…In our recent study [42], oleophobic perfluoropolyether (PFPE) methacrylate molecular bottlebrush (PFM) was synthesized and used as an additive to commodity thermoplastics (nylon 6 and poly(methyl methacrylate)). Our studies showed that an addition of only 1% to 5% of the PFM bottlebrush additives imparts high water and oil repellency to the host thermoplastic matrix.…”
Section: Introductionmentioning
confidence: 99%